An aggregation sensing reporter identifies leflunomide and teriflunomide as polyglutamine aggregate inhibitors - Fuentealba, Rodrigo A. (Oxford University Press, 2012)
Intracellular protein aggregation is a common pathologic feature in neurodegenerative diseases such as Huntington' disease, amyotrophic lateral sclerosis and Parkinson' disease. Although progress towards understanding protein aggregation in vitro has been made, little of this knowledge has translated to patient therapy. Moreover, mechanisms controlling aggregate formation and catabolism in cellulo remain poorly understood. One limitation is the lack of tools to quantitatively monitor protein aggregation and disaggregation. Here, we developed a protein-aggregation reporter that uses huntingtin exon 1 containing 72 glutamines fused to the N-terminal end of firefly luciferase (httQ72-Luc). httQ72-Luc fails to aggregate unless seeded by a non-luciferase-containing polyglutamine (polyQ) protein such as Q80-cfp. Upon co-aggregation, httQ72-luc becomes insoluble and loses its enzymatic activity. Using httQ72-Luc with Q80(CFP/YFP) as seeds, we screened the Johns Hopkins Clinical Compound Library and identified leflunomide, a dihydroorotate dehydrogenase inhibitor with immunosuppressive and anti-psoriatic activities, as a novel drug that prevents polyQ aggregation. Leflunomide and its active metabolite teriflunomide inhibited protein aggregation independently of their known role in pyrimidine biosynthesis, since neither uridine treatment nor other pyrimidine biosynthesis inhibitors affected polyQ aggregation. Inducible cell line and cycloheximide-chase experiments indicate that these drugs prevent incorporation of expanded polyQ into an aggregate. This study demonstrates the usefulness of luciferase-based protein aggregate reporters for high-throughput screening applications. As current trials are under-way for teriflunomide in the treatment of multiple sclerosis, we propose that this drug be considered a possible therapeutic agent for polyQ diseases.